Underlying reasons why some people haven't tested for HIV - a discourse analysis of qualitative data from Cape Town, South Africa - Kyla Meyerson; Graeme Hoddinott; Tamryn Nicholson; Sue-Ann Meehan (Taylor & Francis Group, 2021)
Reported barriers to HIV testing over the last 15 years have remained consistent, despite improved service offerings. We aimed to probe deeper by exploring how people who have never tested construct HIV testing in their talk. We used this to suggest underlying psychosocial barriers to testing even when there is high availability. We enrolled 14 participants who reported that they had never tested for HIV and conducted individual, open-ended interviews. The data were organised thematically with theory-generative interpretations informed by discourse analysis. Reasons for not testing reported reflect similar barriers identified in previous research. Deeper probing identified three discursive processes by which participants explained why they had never tested for HIV, suggesting that the way participants used 'reasons' in their talk is an indicator that the participants were repeating 'tropes'. While aware of HIV testing facilities, participants still chose not to test. Influences on the choice to test or not were positioned as outside of the person's control. These findings suggest that there are deeper reasons why some people have not tested and that these will not be resolved through merely increasing accessibility to testing services. We recommend increased consideration of the psychosocial implications of testing in service delivery.